Vectorial channel estimation for uplink MC-CDMA in beyond 3G wireless systems - Marques, P. (2012)
In beyond 3G wireless systems the bandwidth efficiency can be increased with the use of adaptive antenna arrays. This paper focus on a key issue for adaptive antenna arrays, that is, channel parameters estimation including Direction-Of-Arrival (DOA). In order to estimate DOA. the channel frequency responses for the links between the mobile users and each of base station array elements are estimated by pilot-aided minimum mean square error (MMSE) algorithm. This estimator is not sensitive to the channel statistics. Based on frequency response estimatives DOA's of impinging multipath components to the base station are estimated by a low complex Wlauimuni Likelihood (ML) approach. Furthermore an uplink burst structure with specifically designed midamble field for multiuser channel estimation in MC-CDMA is proposed. The performance is assessed in terms of channel estimation errors for a MC-CDMA TDD system over fast and slow fading mobile channels.